Study of liver function tests and spontaneous bacterial peritonitis in a patients of liver cirrhosis - Mangudkar, Sangram S.; Shivnitwar, Sachin K.; Gokhale, Vijayashree S.; Ithape, Ameya A. (International Journal of Advances in Medicine, 2020)
Background: Liver cirrhosis patients are highly susceptible to bacterial infections specially Spontaneous bacterial peritonitis (SBP) which is commonest infection. this study undertaken to understand liver function tests and Spontaneous bacterial peritonitis in patients of liver cirrhosis admitted to tertiary care hospital. Methods: A descriptive cross-sectional study conducted among Liver cirrhosis patients in tertiary care center. Total 100 liver cirrhotic patients were included in present study. All the patients were subjected for biochemical evaluation of Serum albumin and globulin level, Serum bilirubin, SGOT (Serum glutamic oxaloacetic transaminase), SGPT (Serum glutamic pyruvate transaminase) and Ascitic fluid polymorph nuclear neutrophil (PMN) count to diagnose SBP. Results: Spontaneous bacterial peritonitis was present in 12% patients. Relation of Serum bilirubin level and SBP was statistically significant. Relation of serum SGOT, SGPT level and serum globulin between SBP and non-SBP group was statistically non-significant. Conclusions: Liver cirrhosis patients are susceptible for bacterial infections because of defects in various host defense mechanism and hence patients of liver cirrhosis must be screened for spontaneous bacterial peritonitis along with liver function tests.